Approach to a conceptualization of fundamental rights - Delgado Motoa, Beatriz (DIXI, 2019)
Objective: the essay is aimed at clearly establishing the concept of fundamental rights, based on the differentphilosophical currents that guide the subject, as well as being able to determine it in the countries that makeup Unasur. Methodology: the article study what are the different existing notions about these, which are considered asfundamental. Results: the world, and especially this region, has made great progress in the protection of fundamental rights. Conclusions: the approximation of a common concept to all these countries is presented, in order to achieveits protection in a uniform way.
Keywords: fundamental rights; constitutional guarantees; Unasur